Quality assessment of economic evaluations of health promotion programs for children and adolescents: A systematic review using the example of physical activity - Katharina Korber (Health Economics Review, 2015)
An increasing number of primary prevention programs aimed at promoting physical exercise in children and adolescents are being piloted. As resources are limited, it is important to ascertain the costs and benefits of such programs. The aim of this systematic review is to evaluate the currently available evidence on the cost-effectiveness of programs encouraging physical activity in children and adolescents and to assess their quality. A systematic review was conducted searching in well established literature databases considering all studies before February 2015. Citation tracking in Google Scholar and a manual search of the reference lists of included studies were used to consolidate this. The fundamental methodological elements of the included economic evaluations were extracted, and the quality of the included studies was evaluated using the Pediatric Quality Appraisal Questionnaire (PQAQ). In total, 14 studies were included. Considering the performance of the economic evaluation, the studies showed wide variation. Most of the studies used a societal perspective for their analyses and discounted costs and effects. The findings ranged from US11.59 for a person to become more active (cheapest intervention) up to US669,138 for a disability adjusted life year (DALY) saved (most expensive intervention), with everything in between. Overall, the results of three studies are below a value of US3061, with one of them even below US200.00, for the achieved effects. For the other programs, the context-specific assessment of cost-effectiveness is problematic as there are different thresholds for cost-effectiveness in different countries or no clearly defined thresholds at all. There are multiple methodological difficulties involved in evaluating the cost-effectiveness of interventions aimed at increasing physical activity, which results in little consistency between different evaluations. The quality of the evaluations ranged from poor to excellent while a large majority of them was of very good methodological quality. Better comparability could be reached by greater standardization, especially regarding systematic consideration of implementation costs.
Keywords: 330; Review; Economic evaluation; Physical activity; Children and adolescents; Primary prevention; Health promotion